Comparison of the Frequency of Neonatal Anemia in Early Versus Delayed Cord Clamping in Babies at Term - Shaista Mukhtar, Nimra Bashir, Farzana Sabir, Sara Akram, Nasreen Akhtar, Rohana Salam, Shazia Saeed, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare frequency of the anemia in neonates in early versus delayed umbilical cordclamping in term infants. Study design: Randomized controlled trial. Place and duration of study: Department of Obstetrics & Gynecology, Divisional Headquarters Hospital Mirpur AJK from 30th January 2021 to 29th July 2021. Methodology: The study enrolled 96infants which were delivered at term within the gestational range of 37-41 weeks (as assessed on LMP). Those infants who were born to diabetic, sepsis mother or with inborn metabolic errors, jaundice neonatorum or Rh incompatibility and PROM were excluded from the study. Then selected women were placed randomly into two equal groups i.e. Group A (early cord clamping) & Group B(delayed cord clamping) by lottery method. Respective group selection was performed through randomization. In group a neonates, early cord clamping (cord clamping within 15 seconds of birth) was done while in group B neonates, delayed cord clamping (cord clamping after 3 minutes of birth) was done. In both groups, blood sample of all infants was sent after 6 hours of birth for hematocrit level measurement and neonatal anemia was noted. Results: The mean age in years of patients in group A was calculated as 26.52±5.17 while in group B it was calculated as 27.17±3.89. The age of 80.21% patients was within 18 to 30 years and the mean gestational age was determined as 39.23±1.48 weeks. The mean gestational age in group A was 39.25±1.48 weeks and in group B was 39.21±1.49 weeks. Frequency of neonatal anemia in group A (early cord clamp) versus group B (delayed umbilical cord clamping) was 11 (22.92%) and 04 (8.33%) respectively with p-value of 0.049. Practical Implication: we recommend that delayed umbilical cord clamping should be preferred in our routine practice for prevention of neonatal anemia. Conclusion: This study concluded that the neonatal anemia is high after early cord clamping in infants at term as compared to delayed cord clamping Keywords: Cord Clamping, Delayed, Anemia.